Mesoscale mechanical model for intergranular stress corrosion cracking and implications for microstructure engineering - Jivkov, A; Stevens, N; Marrow, T (2008)
The resistance of polycrystalline materials to intergranular cracking can be influenced by the microstructure. In sensitized stainless steels, for example, the grain boundaries prone to sensitization form paths of low resistance for intergranular stress corrosion cracking. The nonsensitized grain boundaries, such as twin boundaries, have been observed to encourage the formation of crack bridging ligaments. Computational models of intergranular cracking have been developed to investigate the consequences of crack bridging, through its effects on crack propagation in microstructures with different fractions of nonsensitized boundaries. This paper introduces the recently developed, two-dimensional model for intergranular cracking with crack bridging, and reports its application to investigate the effect of grain size. It is shown that the size of the crack bridging zone depends on the grain size, and the shielding contribution depends on the relative size of the bridging zone compared to the crack length. It is concluded that both grain refinement and increase in the fraction of resistant boundaries can improve microstructure resistance to intergranular cracking. These observations are consistent with the effects of grain boundary engineering on stress corrosion cracking resistance in sensitized stainless steels. Copyright © 2008 by ASME.